Cholesterol catabolism as a therapeutic target in Mycobacterium tuberculosis - Ouellet, Hugues (2011)
Mycobacterium tuberculosis (Mtb) is an intracellular pathogen that infects 10 million worldwide and kills 2 million people every year. The uptake and utilization of nutrients by Mtb within the host cell is still poorly understood, although lipids play an important role in Mtb persistence. The recent identification of a large regulon of cholesterol catabolic genes suggests that Mtb can use host sterol for infection and persistence. In this review, we report on recent progress in elucidation of the Mtb cholesterol catabolic reactions and their potential utility as targets for tuberculosis therapeutic agents.